Pengaruh Model Pembelajaran Cooperative Tipe Script Terhadap Kemampuan Berkomunikasi Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas V UPTD SDN 178 Barru - Rahma, Sulistia; Akib, Tasrif; Anzar, Anzar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The main problem in this research is that learning activities are still focused on the teacher, students lack focus in learning and often complain of being bored in learning, resulting in low communication skills in Indonesian language subjects. This research aims to determine the effect of the script type cooperative learning model on communication skills in class V Indonesian language subjects at UPTD SDN 178 Barru. This type of research is Quasi Experimental Design research and is a quantitative type of research. The sample in this study was 10 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test. The results of the research show that communication skills in Indonesian language subjects before implementing the script type cooperative learning model in the pretest with an average score of 67. Meanwhile in the posttest it increased with an average score of 83. Results of t-test analysis on the influence of the script type cooperative learning model on the learning outcomes of student participants showed that the significance value obtained was good, namely the influence of the script type cooperative learning model on communication skills in Indonesian language subjects (Sig = 0.012) was smaller than the alpha value set, namely 0.05 (0.012 < 0.05 ). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted which states that there is an influence of the Script Type Cooperative Learning Model on Students' Communication Ability in Class V Indonesian Language Subjects at UPTD SDN 178 Barru